Activated Carbon-Supported Lipase as Biocatalyst for Biodiesel Synthesis from Crude Palm Oil - Rachmadona, Nova; Zahrah, Fasya Nur Aulia; Dewi, Dewa Ayu Shintya Laura Arista; Hartono, Agus Try; Kurnia, Irwan; Noviyanti, Atiek Rostika; Zikri, Ahmad; Restu, Witta Kartika (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
Biodiesel is a renewable energy source with significant potential to reduce reliance on fossil fuels. In its production, crude palm oil (CPO) is commonly processed through transesterification, a reaction often catalyzed by lipase enzymes. While these enzymes are effective, their single-use nature results in high production costs. To address this issue, immobilizing lipase enzymes on activated carbon offers a promising solution, enabling the reuse of the enzyme and reducing costs. This study aimed to evaluate the effectiveness of activated carbon as a support for lipase immobilization in biodiesel production from CPO. The immobilization process involved incubating 1 g of activated carbon with 1 mL of lipase and 9 mL of 0.01 M Tris HCl buffer at 30°C for 6 h. The morphology of the immobilized lipase on activated carbon was analyzed using transmission electron microscopy (TEM) and the immobilized lipase exhibited a catalytic activity of 2.95 U/mg. Biodiesel synthesis was carried out with 50 g of CPO and 3 g of immobilized lipase as a catalyst, at 30°C for 24 h, with gradual methanol addition. The biodiesel was then analyzed, showing an acid value of 1.94 mg-NaOH/g, a saponification value of 143.61 mg-KOH/g, a free glycerol content of 0.06%-mass, a total glycerol content of 0.23%-mass, an ester content of 95.70%, a density of 872.09 kg/m³ at 40°C, and a kinematic viscosity of 6 mm²/s at 40°C. This study offers a more sustainable and cost-effective method for biodiesel production, highlighting the potential of immobilized enzymes to enhance renewable energy practices.